A Practical Guide to Distributed Scrum - and Woodward, Elizabeth; Surdek, Steffan; Ganis, Matthew (IBM Press, 2010)
Succeed with Scrum in Even the Largest, Most Complex Distributed Development Projects Forewords by Ken Schwaber, Scott Ambler, Roman Pichler, and Matthew Wang This is the first comprehensive, practical guide for Scrum practitioners working in large-scale distributed environments. Written by three of IBM’s leading Scrum practitioners–in close collaboration with the IBM QSE Scrum Community of more than 1000 members worldwide–this book offers specific, actionable guidance for everyone who wants to succeed with Scrum in the enterprise. Readers will follow a journey through the lifecycle of a distributed Scrum project, from envisioning products and setting up teams to preparing for Sprint planning and running retrospectives. Each chapter presents a baseline drawn from “conventional” Scrum, then discusses additional issues faced by distributed teams, and presents specific best-practice solutions, alternatives, and tips the authors have identified through hard, empirical experience. Using real-world examples, the book demonstrates how to apply key Scrum practices, such as look-ahead planning in geographically distributed environments. Readers will also gain valuable new insights into the agile management of complex problem and technical domains. Coverage includes Developing user stories and working with Product Owners as a distributed team Recognizing and fixing the flaws Scrum may reveal in existing processes Engaging in more efficient Release and Sprint planning Conducting intense, brief daily Scrum meetings in distributed environments Managing cultural and language differences Resolving dependencies, performing frequent integration, and maintaining transparency in geographically distributed environments Successfully running remote software reviews and demos Brainstorming what worked and what didn’t, to improve future Sprints This book will be an indispensable resource for every team leader, member, product owner, or manager working with Scrum or other agile methods in any distributed software development organization.